Copper-catalyzed asymmetric methylation of fluoroalkylated pyruvates with dimethylzinc - Aikawa, Kohsuke; Yabuuchi, Kohei; Torii, Kota; Mikami, Koichi (Beilstein Journal of Organic Chemistry, 2018)
The catalytic asymmetric methylation of fluoroalkylated pyruvates is shown with dimethylzinc as a methylating reagent in the presence of a copper catalyst bearing a chiral phosphine ligand. This is the first catalytic asymmetric methylation to synthesize various α-fluoroalkylated tertiary alcohols with CF3, CF2H, CF2Br, and n-CnF2n+1 (n = 2, 3, 8) groups in good-to-high yields and enantioselectivities. Axial backbones and substituents on phosphorus atoms of chiral phosphine ligands critically influence the enantioselectivity. Moreover, the methylation of simple perfluoroalkylated ketones is found to be facilitated by only chiral phosphines without copper.
Keywords: asymmetric methylation; chiral phosphine ligand; copper catalyst; dimethylzinc; trifluoropyruvate